Populationsstruktur och genetisk analys av exteriöra egenskaper hos svensk ardenner - Siekas, Ann-Charlott (2006)
The purposes of this study were to estimate genetic and phenotypic parameters for conformation traits in Swedish Ardenner, a heavy draught horse, and to investigate the inbreeding status of the population. Additionally, a breeding scheme proposal was created, based on the results achieved in the study.